Faktor Yang Mempengaruhi Financial Management Behavior Pada Mahasiswa Fokus Keilmuan Ekonomi Dan Bisnis Kabupaten Gresik - Yanuar Trisnowati; Marisya Mahdia Khoirina; Firda Alvina Putri (Jurnal Manajerial, 2020)
Background – College students are one component of society that plays an important role for the change of the nation (agent of change). At this moment they are in a situation where they face financial independence and start making responsible decisions. Financial education can be done by providing understanding to the public, especially the younger generation about finances and their management that is good and wise, that is why, financial knowledge is needed. Today's society tends to buy things as they wish, so, financial knowledge requires skills and tools for individuals to be able to provide financial decisions and with confidence can manage individual welfare efficiently. Good personal financial management must have at least knowledge so that individuals can apply their knowledge based on their financial attitudes. Purpose - Determine and analyze the factors that influence the behavior of financial management of college students, focusing on Economics and Business, in Gresik Regency. Design / methodology / approach – This research methodology uses a descriptive quantitative approach. Chosen population was 2,636 college students and the sample used was 347 students. Data collection taken by questionnaires and analysis was using multiple linear regression. Finding - Three research variables (1) Financial Attitude, (2) Financial Knowledge, and (3) Locus of Control have an influence on the Financial Management Behavior. College students who tend to have a good financial attitude then they have good financial behavior in managing personal finances. College students with financial knowledge will better understand financial problems and be better in terms of financial behavior. College students who have a good locus of control will be able to measure the risks that occur so that they can easily make a decision and their finances tend to have a level of trust, confidence and good control over their financial management. Research Implication – This research has implications for assessing student behavior in managing personal finances in an effort to meet the needs of education and daily life. Limitation – In assessing financial management behavior (Financial Management Behavior), this research student only uses 3 variables, namely Financial Attitude, Financial Knowledge, and Locus of Control.